The Effect of Photoperiod on Growth, and Protein, Lipid and Chlorophyll Content in Scenedesmus Acutus - Kaymaz, Nur Ağırman; Cetin, Ahmet Kadri (My University, 2020)
The effect of photoperiod on the growth, protein, lipid and pigment content in Scenedesmus acutus was examined on cultures exposed to 23 ± 1 °C for ten days at the light intensity of 55 µmol photon m-2s-1. Results showed that photoperiods had an effect on cell number, and protein and chlorophyll content. The growth, protein, lipid and chlorophyll levels in Scenedesmus acutus cultures reached maximum in different days and photoperiods. The number of cells of the continuously illuminated cultures was highest on day seven after inoculation. The total protein and total lipid content were highest on day eight under the light/dark photoperiod of 20/4 h while total chlorophyll content was highest on day ten under the light/dark photoperiod of 24:0 h. The cultures continuously illuminated for cell growth had the highest specific growth rate (µ=0.2304). Protein content had a specific growth rate of µ=0.0725 under the light/dark photoperiod of 20/4 h while total chlorophyll content had a specific growth rate of µ=0.0890 under the light/dark photoperiod of 12:12-h.
Keywords: Scenedesmus acutus; growth; lipid; photoperiod; Green algae